Sustainable Production and Physicochemical Characteristics of Calcium Sulfate Dihydrate Prepared from Waste Eggshells - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Nongnuch Laohavisuti; Wimonmat Boonmee; Pesak Rungrojchaipon; Phairat Phimsirikul (Crystals, 2024)
Gypsum products (calcium sulfate dihydrate, CaSO4·2H2O) were synthesized through an eco-friendly and low-cost process by two different renewable calcium carbonate sources (CaCO3), hen and duck eggshell wastes, with product yields obtained of 84.73 and 87.74%, respectively. The X-ray fluorescence results indicated that calcium oxide (CaO) and sulfur trioxide (SO3) are the major elemental components of CaSO4·2H2O prepared from both calcium sources. The Fourier transform infrared results confirmed the vibrational characteristics of SO42− and H2O functional groups in the chemical structure of the prepared samples. The X-ray diffraction patterns of CaSO4·2H2O prepared from both calcium sources confirmed the sample’s crystal structure as well as the chemical formula, after comparing them to the standard powder diffraction file. The crystallite sizes of CaSO4·2H2O products were calculated from the experimental diffraction peak through the Scherrer equation and found to be 19–20 nm. The positive preferential growth (Pg) value highlighted the excellent stability of the synthesized CaSO4·2H2O. The scanning electron microscopic results showed the agglomeration particles of hen- and duck-CaCO3 raw agents, whereas plate-like particles were observed for hen- and duck-CaSO4·2H2O products but the particle sizes were different.
Keywords: Phosphorus and nutrient management; Chemical and Physical Properties in Aqueous Solutions; Crystallization and Solubility Studies